New mini-ColE1 as a molecular cloning vehicle. - Avni, H (1977)
A new mini-ColE1 plasmid, designated pAC105, was isolated. It has a molecular weight of 1.6 X 10(6) and carries information for its self-replication as well as information for conferring colicin E1 immunity upon its host. Furthermore, pAC105 undergoes replication in the presence of chloramphenicol even when a foreign deoxyribonucleic acid (pSC101) is inserted into its single EcoRI restriction site. Studies in minicell-producing strains demonstrate that pAC105 codes for only two or three polypeptides of low molecular weight. The advantages of using it as a molecular cloning vehicle are discussed.